Old Growth Urban Forests - Loeb, Robert E.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
No back cover.
(1) What and Where Are Old Growth Urban Forests? -- (2) Historical Continuity -- (3) Partnerships, Adaptive Management, and Restoration for Historical Continuity -- Index.
Keywords: Life sciences; Ecology; Urban Ecology; Forests and forestry; Nature Conservation; Life Sciences; Terrestial Ecology; Urban Ecology; Forestry Management; Nature Conservation